2014
DOI: 10.1542/peds.2013-2932
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Caregivers and Children’s Entry Into the Dental Care System

Abstract: OBJECTIVES: Early preventive dental visits are essential in improving children’s oral health, especially young children at high risk for dental caries. However, there is scant information on how these children enter the dental care system. Our objectives were as follows: (1) to describe how a population-based cohort of young Medicaid-enrolled children entered dental care; and (2) to investigate the influence of caregiver characteristics on their children’s dental care–seeking patterns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 45 publications
1
53
0
Order By: Relevance
“…This finding seems to be associated with the difficulty of understanding such measures on the part of parents/caregivers, or else the low priority given to oral health care. 29 In this respect, one must consider the influence of environmental and socioeconomic factors. While families may agree to follow the recommendations of dental professionals for the maintenance of their children's oral health, aspects such as level of comprehension and poor living conditions, as well as limited availability and access to health services may compromise the adoption and success of preventive measures.…”
mentioning
confidence: 99%
“…This finding seems to be associated with the difficulty of understanding such measures on the part of parents/caregivers, or else the low priority given to oral health care. 29 In this respect, one must consider the influence of environmental and socioeconomic factors. While families may agree to follow the recommendations of dental professionals for the maintenance of their children's oral health, aspects such as level of comprehension and poor living conditions, as well as limited availability and access to health services may compromise the adoption and success of preventive measures.…”
mentioning
confidence: 99%
“…As pointed out by two other studies conducted in the USA -one that assessed emergency care at a university health center and one that investigated into Medicaid beneficiaries, first access of children to oral health systems due to a dental emergency shows a remarkable rate [19,20]. Several parents/legal guardians seek first dental care for their children when they spot a problem [21,22] and there have been reports that children with worse oral health have a higher prevalence of first access to the health system during emergency care than those with a better oral health status [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several parents/legal guardians seek first dental care for their children when they spot a problem [21,22] and there have been reports that children with worse oral health have a higher prevalence of first access to the health system during emergency care than those with a better oral health status [20].…”
Section: Discussionmentioning
confidence: 99%
“…This line of research also found oral health literacy associations with oral health status, oral health-related behaviors, knowledge, and quality of life. Importantly, it highlighted that low health literacy among caregivers was associated with children having worse oral health status, deleterious oral health behaviors (e.g., no daily brushing/cleaning and nighttime bottle use), suboptimal use of dental services, and interruptions in children's public insurance coverage (Vann et al, 2010;Lee et al, 2012;Divaris et al, 2014). Self-efficacy and dental neglect are 2 behavioral constructs that have emerged as important mediators between literacy and oral health outcomes (Lee et al, 2012).…”
Section: Advances In Genetics and Pediatric Oral Health Applicationsmentioning
confidence: 99%